The Effectiveness of a Drug Abuse Prevention Module Based on Self-Assertiveness, Spirituality and Belief in the Detriments of Drug Abuse (MPDASK) - Amin Al Haadi Shafie; Durrah Athirah Walid; Abdul Rashid Bin Abdul Aziz; Nurhafizah Mohamad Yassin; Dini Farhana Bt Baharudin; Khatijah Othman; Rafidah Aga Bt Mohd Jaladin; Salleh Amat; Suzaily Wahab (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2023)
A study on the effectiveness of a spirituality-based drug and substance abuse prevention module was carried out by researchers on youth living in a high-risk area in the north of Peninsular Malaysia. The study was done to investigate the effectiveness of the spiritual drug abuse prevention module based on (1) self-assertiveness, (2) spirituality, and (3) their belief concerning substance and drug abuse. The study sample was divided into an experimental and control group for the pre and post stages. This study used a quasi-experimental design involving two youth groups from different zones, each consisting of 33 people (experimental and control groups). A psychoeducational intervention of seven meeting sessions was carried out on the experimental group, while the control group was not given any intervention. The results of the pre-and post-test comparison showed that there was a significant increase in the mean value of self-assertiveness (mean value from pre-test 99.45 to 106.42 post-test), spirituality (mean value from pre-test 172.24 to 188.12 post-test) and beliefs about drug abuse (mean value from pre-test 28.91 to 41.48 post-test) for the experimental group that went through the intervention given by the trained facilitator using this spirituality module. The mean results of the control group showed no mean increase for the three variables studied. In conclusion, the spiritual module for preventing drug abuse can help the youth from being involved in substance and drug abuse and enjoy a more positive life.